Kairos consciousness and the Zimbabwean ecclesiology"s response to crisis - Paradza, Kudakwashe (HTS teologiese studies, 2019)
The Christian church in Zimbabwe radically indicated the courage and consciousness to identify itself with the struggle for liberation of the marginalised, the oppressed and the impoverished, more specifically in the context of chimurenga or the armed struggle. Thus, the Kairos model of ecclesiology consistently and unequivocally supported masses who were the majority Zimbabweans during the protracted struggle of the 1970s against racial system, thereby assuming such designations as the church of struggle, the Church of chimurenga, the church in trenches and combat with the people; hence, the liberationist language signalled a symbol of Kairos consciousness for Zimbabwean ecclesiology. Kairos consciousness implies the liberationist methodological framework of ecclesiology when the church becomes the interlocutor and articulator identified and associated with non-persons. Furthermore, the non-persons, the impoverished and the marginalised occupy the epicentre of epistemological space in ecclesiological discourse. Precisely, the socio-economic and political landscape of Zimbabwe radically shifted from 2000 onwards, marking the genesis of a crisis. This article based on ecclesiology investigates prophetic role and the impact of the church in the context of Zimbabwean crisis.